1995
DOI: 10.1006/jaar.1995.1004
|View full text |Cite
|
Sign up to set email alerts
|

Reasserting a Prehistoric Tragedy of the Commons: Reply to Lyman

Abstract: AND WU.UAM R. HlI.nmm.ANDT far Wcs/t'1"/I A/lt/lwl'll/llgiml UC~l'lIrdl CrollJI, OIlP;S, Californill 95(,17 R. Lee Lyman has challenged our assertion that prehistoric hunting of marine mammals along the west coast of North America approximated a prehistoric tragedy of the commons in which highly ranked migratory sea lions and fur seals were reduced by overexploitation, necessitating pursuit of smaller, more elusive harbor seals and sea otters late in time. In response, we review alternative theoretical perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 5 publications
(13 reference statements)
3
44
1
1
Order By: Relevance
“…Whether related to pa leoclimatic events (San Clemente Island is very poorly watered, and modest de creases in frequency/amount of rainfall could easily render all or parts of the is land uninhabitable) or some other phe nomenon, this hiatus may have given ma rine mammal populations a chance to recover from earlier exploitation, and re newed occupation brought with it heavy exploitation of rookeries. This scenario is similar to the one advanced by Jones and Hildebrandt (1995) to explain an apparent rebound in non-terrestrial breeder popu lations on the northern Channel Islands ca. A.D.1200 when so-called "Medieval droughts" (Graumlich 1993;Raab and Larson 1997;Stine 1994) disrupted settle ment on the more poorly watered islands (Arnold 1992b).…”
Section: Patterns Through Timesupporting
confidence: 79%
See 3 more Smart Citations
“…Whether related to pa leoclimatic events (San Clemente Island is very poorly watered, and modest de creases in frequency/amount of rainfall could easily render all or parts of the is land uninhabitable) or some other phe nomenon, this hiatus may have given ma rine mammal populations a chance to recover from earlier exploitation, and re newed occupation brought with it heavy exploitation of rookeries. This scenario is similar to the one advanced by Jones and Hildebrandt (1995) to explain an apparent rebound in non-terrestrial breeder popu lations on the northern Channel Islands ca. A.D.1200 when so-called "Medieval droughts" (Graumlich 1993;Raab and Larson 1997;Stine 1994) disrupted settle ment on the more poorly watered islands (Arnold 1992b).…”
Section: Patterns Through Timesupporting
confidence: 79%
“…Quantified data from southern California were largely limited to findings from the breeding colony on San Miguel Island, and were more equivocal, as terrestrial breeders initially declined, but later showed some signs of a population re bound. Jones and Hildebrandt (1995) sug gested that prolonged droughts during the early centuries of the present millen nium (see Graumlich 1993;Stine 1994) may have forced humans to abandon some or all of the more poorly watered Channel Islands, giving marine mammal populations opportunity for both short and long-term recovery.…”
Section: Alternative Perspectives On Marine Mammal Exploitationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some workers attribute the decline to climate change (Glassow 1993;Colten and Arnold 1998); others blame predation by aboriginal hunters (Hildebrandt and Jones 1992;Jones and Hildebrandt 1995). If climate change were responsible, it must have been transient, as northern fur seals maintained island rookeries in the region into historic times.…”
Section: Discussionmentioning
confidence: 99%